The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.03.20.000091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The BBSome assembly is spatially controlled by BBS1 and BBS4 in human cells

Abstract: Bardet-Biedl Syndrome (BBS) is a pleiotropic ciliopathy caused by dysfunction of primary cilia.Most BBS patients carry mutations in one of eight genes encoding for subunits of a protein complex, BBSome, which mediates the trafficking of ciliary cargoes. Although, the structure of the BBSome has been resolved recently, the mechanism of assembly of this complicated complex in living cells is poorly understood. We generated a large library of human retinal epithelial cell lines deficient in particular BBSome subu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, analysis of the dynamic behavior of the BBSome throughout the primary cilium demonstrated a rapid recovery (halftime of 2-6 seconds) in a photobleaching assay, indicating that the BBSome complex has a relatively fast turnover rate. 73 Said data suggest that the WT BBS1 protein is assembled de novo into the BBSome rather than replacing the mutant BBS1 protein in the pre-existing BBSome. However, further mechanistic studies are needed to better understand the dynamics of BBSome in OSNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, analysis of the dynamic behavior of the BBSome throughout the primary cilium demonstrated a rapid recovery (halftime of 2-6 seconds) in a photobleaching assay, indicating that the BBSome complex has a relatively fast turnover rate. 73 Said data suggest that the WT BBS1 protein is assembled de novo into the BBSome rather than replacing the mutant BBS1 protein in the pre-existing BBSome. However, further mechanistic studies are needed to better understand the dynamics of BBSome in OSNs.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, we were able to rescue the olfactory deficits in the Bbs1 M390R/M390R mice, suggesting that proper function of the BBSome can be restored by ectopic WT Bbs1 expression. Interestingly, analysis of the dynamic behavior of the BBSome throughout the primary cilium demonstrated a rapid recovery (halftime of 2‐6 seconds) in a photobleaching assay, indicating that the BBSome complex has a relatively fast turnover rate 73 . Said data suggest that the WT BBS1 protein is assembled de novo into the BBSome rather than replacing the mutant BBS1 protein in the pre‐existing BBSome.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Meier survival analysis was used to plot overall survival (OS). The hazard ratio (HR) of the 95 % confidence intervals (CI) will be computed using Cox proportional hazard regression analysis to test the relationship between BBS4 expression level and a stable protein complex, called BBSome, which is a binding protein complex composed of BBS1, 2, 4, 5, 7, 8, 9 and 18, which is structurally similar to the coat protein or adapter protein involved in vesicle transport [4][5][6] . Bardet-Biedl syndrome 4 (BBS4) is one of several proteins that cause BBSome.…”
Section: Discussionmentioning
confidence: 99%
“…For this experiment, we used mechanically isolated OSs of 5 month old zygotic bbs1 -/fish and their wildtype siblings as controls (Fig. 5a), which we submitted to label-free quantitative MS-MS. BBS4 and BBS1 are thought to play a key role in the spatial regulation of the full BBSome complex assembly 51 restricting the entry of the complex into the cilium in the absence of BBS1 52 . However, a recent publication suggested that photoreceptor cilia, in contrast to primary cilia, grant entry to a partially assembled BBSome 53 .…”
Section: Accumulation Of Membrane-associated Proteins In Mutant Outer Segmentsmentioning
confidence: 99%